2021
DOI: 10.1021/acsami.0c21507
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mesoporous Silica Nanoparticles to Overcome Biological Barriers by Incorporating Targeting and Endosomal Escape

Abstract: The several biological barriers that nanoparticles might encounter when administered to a patient constitute the major bottleneck of nanoparticle-mediated tumor drug delivery, preventing their successful translation into the clinic and reducing their therapeutic profile. In this work, mesoporous silica nanoparticles have been employed as a platform to engineer a versatile nanomedicine able to address such barriers, achieving (a) excessive premature drug release control, (b) accumulation in tumor tissues, (c) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 69 publications
(104 reference statements)
0
41
0
Order By: Relevance
“…1000 m 2 /g), high pore volumes (ca. 1 cm 3 /g), biocompatibility, and facile surface modification 18 , 19 . The fabrication of MSNs is cost-effective and straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…1000 m 2 /g), high pore volumes (ca. 1 cm 3 /g), biocompatibility, and facile surface modification 18 , 19 . The fabrication of MSNs is cost-effective and straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors present high requirements of vitamins, which leads to the overexpression of their receptors on tumoral cells. In this sense, our group recently reported targeted redox-responsive MSNs [ 35 ]. We incorporated a redox-responsive gatekeeper based on self-immolative chemistry and further functionalize it with a peptidic molecule containing biotin (vitamin B7) for cellular targeting and histidine for inducing endosomal escape ( Figure 5 ).…”
Section: Small Molecules As Targeting Agents Of Redox-responsive Msnsmentioning
confidence: 99%
“…( D ) The calcein assay demonstrated that only the group bearing the peptidic molecule was able to escape the endosomes. Adapted with permission from [ 35 ]. Copyright ACS, 2021.…”
Section: Figurementioning
confidence: 99%
“…Effective gene delivery needs to overcome several barriers, including in terms of protection against endogenous nuclease degradation, cellular uptake elevation, and endosomal avoidance [ 80 , 81 ]. However, conventional gene delivery nanoplatforms, such as mesoporous silica nanoparticles, are unable to transfer nucleic acid into host cells due to the failure of endosomal escape [ 82 ]. In this case, bacteria exhibit excellent gene delivery capabilities.…”
Section: A New Role For the Old Playermentioning
confidence: 99%